2009
DOI: 10.1161/circulationaha.108.805465
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Clinical Outcomes, Midterm Survival, and Predictors of Mortality After Carotid Stenting in Elderly Patients

Abstract: Background-It has been demonstrated recently that carotid stenting can be performed safely in patients Ն80 years of age.However, it is uncertain whether these patients will derive benefit because longevity after revascularization is an important consideration. This study was conducted to determine survival and predictors of mortality of selected elderly patients after stenting. Methods and Results-One hundred forty-two consecutive elderly patients who were non-high risk for stenting underwent 153 procedures. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 33 publications
2
27
1
Order By: Relevance
“…Although it is difficult to compare in-hospital and 1-year results from the present study to other investigations because of differences in methodology and study population, the rates of in-hospital stroke and mortality in the present study are similar to those reported in CAS registries and randomized, controlled, clinical trials. 10,[25][26][27][28][29] It may be that mortality is truly increased with CAS relative to CEA. There are reasons, however, to believe that there are more cogent explanations for the mortality difference.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to compare in-hospital and 1-year results from the present study to other investigations because of differences in methodology and study population, the rates of in-hospital stroke and mortality in the present study are similar to those reported in CAS registries and randomized, controlled, clinical trials. 10,[25][26][27][28][29] It may be that mortality is truly increased with CAS relative to CEA. There are reasons, however, to believe that there are more cogent explanations for the mortality difference.…”
Section: Discussionmentioning
confidence: 99%
“…8 This series of patients has previously been reported, with the current article adding observations related to intermediate-term survival. 9 Of these 142 patients, 72% were asymptomatic.…”
Section: Article See P 2343mentioning
confidence: 87%
“…However, there are conflicting results about adverse events associated with carotid stenosis in very elderly patients (Chiam et al., 2009; Hobson et al., 2004; Howard et al., 2016). Early studies showed that adverse events rates in octogenarians undergoing CAS were 25% as compared to 8.2% in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Research demonstrates that 85% of the selected elderly patients survived 2 years and ≥75% survived 3 years after stenting. Therefore, for this group, carotid stenting may be considered as a revascularization option (Chiam et al., 2009). But it is still necessary to evaluate the longer‐term outcomes to better understand the role of CAS in this population and to allow them to gain more benefit from this procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation